Bilateral Radical Nephrectomy & Adrenalectomy – a Rare Case Report - Rakib, Md Abdur; Rashid, Harunur; Islam, Md Shahidul; Waheed, SM Shameem; Chwdhury, Md Ashif; Alam, Mohammad Shafiul (Bangladesh Journal of Urology, 2020)
Abstract Not Available Bangladesh Journal of Urology, Vol. 22, No. 2, July 2019 p.204-205